EKSISTENSI KOMUNITAS SUKABUMI STREET ART DI KOTA SUKABUMI - Muhammad Farhan Nugraha; Agus Sudarmawan; I Gusti Ngurah Sura Ardana (Universitas Pendidikan Ganesha, 2022)
This study uses the theory of existence to find out how the ability of the members of the Sukabumi Street Art community can maintain so that there is development, or vice versa, namely experiencing a decline. This research is one of the research that uses descriptive qualitative. The discussion of this type of research is in the form of a descriptive description by describing the data according to what is happening in the field. The subject of this research is the Sukabumi Street Art Community. The data in this study were obtained using source data which was divided into primary data, namely data obtained from sources, and also secondary data, namely data obtained previously by primary sources. Techniques in collecting this data through observation, interviews, documentation, and keputaskaan. The analysis technique for this data uses data analysis from the Miles and Huberman model which consists of data reduction, data presentation, and drawing conclusions. The results of this study on all members of the Sukabumi Street Art Community regarding